Catatonia and the immune system: a review - Rogers, Jonathan P (Lancet Psychiatry, 2019)
Catatonia is a psychomotor disorder featuring stupor, posturing, and echophenomena. This Series paper examines the evidence for immune dysregulation in catatonia. Activation of the innate immune system is associated with mutism, withdrawal, and psychomotor retardation, which constitute the neurovegetative features of catatonia. Evidence is sparse and conflicting for acute-phase activation in catatonia, and whether this feature is secondary to immobility is unclear. Various viral, bacterial, and parasitic infections have been associated with catatonia, but it is primarily linked to CNS infections. The most common cause of autoimmune catatonia is N-methyl-D-aspartate receptor (NMDAR) encephalitis, which can account for the full spectrum of catatonic features. Autoimmunity appears to cause catatonia less by systemic inflammation than by the downstream effects of specific actions on extracellular antigens. The specific association with NMDAR encephalitis supports a hypothesis of glutamatergic hypofunction in catatonia.